Suggested Conceptualizing Media and Educational Arrangements Counter-terrorism in Saudi Arabia according to the Light of Future Trends - AlSubie, Mohamed Naser; Ismail, Hamdan Mohamed; Mohamed, Mortada AbdAlRahim; Ibrahim, Hamad Mohamed; Gad- AlRab, Fahd Salah (Journal of Educational and Psychological Sciences, 2020)
The current study aimed at developing suggested conceptualizing of media and educational arrangements to counter terrorist crimes in Saudi Arabia. This study used the descriptive, inductive and deductive approaches. The important findings of this study: There is a shortage in the media and educational arrangements to counter terrorist crimes. The important challenges and problems facing media and educational arrangements to counter terrorist crimes are: overlapping factors and conditions that relate to terrorism, international cooperation to counter-terrorism and state sovereignty, integrity of international cooperation objectives, national unity and international security, the citizen's freedoms and rights, measuring economic costs of terrorist crimes, global terrorism, the ideology of media and digital terrorism, continuously of terrorist acts. Finally, suggested conceptualizing of media and educational arrangements to counter terrorist crimes in Saudi Arabia: its philosophy, foundations, and requirements and mechanisms. The most important recommendations of this study are: The need to treat terrorism as primarily an educational and media issue, the importance of creating a unified national vision, strategy, standards and qualified national cadres in the fields of media and education to counter-terrorism. * تم تمويل هذه الدراسة برعاية عمادة البحث العلمي، جامعة الطائف، المملكة العربية السعودية رقم المشروع البحثي (6066- 439- 1) والباحثون يتقدمون بأسمى آيات الشكر والتقدير للجامعة على هذا الدعم الإداري والفني.
Keywords: Media arrangements; Educational arrangements; counter terrorism; Suggested conceptualizing; Future Trends; Saudi Arabia